Tubal Factor Infertility, In Vitro Fertilization, and Racial Disparities: A Retrospective Cohort in Two US Clinics. Issue 10 (October 2021) - Anyalechi, Gloria E.; Wiesenfeld, Harold C.; Kirkcaldy, Robert D.; Kissin, Dmitry M.; Haggerty, Catherine L.; Hammond, Karen R.; Hook, Edward W.; Bernstein, Kyle T.; Steinkampf, Michael P.; Geisler, William M.
Abstract : For Black versus White women, tubal infertility was twice as common with, 7% (95% confidence interval, 1–30%) starting in vitro fertilization versus 31% (95% confidence interval, 17–49%). Supplemental digital content is available in the text. Abstract : Background: Nearly 14% of US women report any lifetime infertility which is associated with health care costs and psychosocial consequences. Tubal factor infertility (TFI) often occurs as a result of sexually transmitted diseases and subsequent pelvic inflammatory disease. We sought to evaluate for and describe potential racial disparities in TFI and in vitro fertilization (IVF) prevalence. Methods: Records of women aged 19 to 42 years in our retrospective cohort from 2 US infertility clinics were reviewed. We calculated TFI prevalence, IVF initiation prevalence, and prevalence ratios (PRs), with 95% confidence intervals (CIs) for each estimate, overall and by race. Results: Among 660 infertile women, 110 (16.7%; 95% CI, 13.8–19.5%) had TFI which was higher in Black compared with White women (30.3% [33/109] vs 13.9% [68/489]; PR, 2.2 [95% CI, 1.5–3.1]). For women with TFI, IVF was offered to similar proportions of women by race (51.5% [17/33] vs 52.9% [36/68] for Black vs White women); however, fewer Black than White women with TFI started IVF (6.7% [1/15] vs 31.0% [9/29]; PR, 0.2 [95% CI, 0–1.0]), although the difference was not statistically different. Conclusions: Tubal factor infertility prevalence was 2-fold higher among Black than White women seeking care for infertility. Among women with TFI, data suggested a lower likelihood of Black women starting IVF than White women. Improved sexually transmitted disease prevention and treatment might ameliorate disparities in TFI.